Análise descritiva dos lançamentos previdenciários do Cadastro Nacional de Informaç\~oes Sociais - Marcos Antonio Coutinho da Silveira; Ajax Reynaldo Bello Moreira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– It is almost a consensus that the ongoing transformations in the Brazilian demographic structure press for urgent changes in the current social security rules as the objective of guaranteeing the actuarial balance of the national pension system. It is therefore important to predict the impact of proposed alterative rules on the future trajectories of contribution revenues and benefits expenditures. This task can be done with the help of a random sample of the individuals present in the National Register of Social Information (CNIS): an administrative file with the history of contributions and social security benefits of the participants of the General Social Security Regime (RGPS). The file also has information on relevant personal characteristics of these individuals, such as gender, age and year of birth, which can be used to estimate the probabilities of contribution and receipt of benefits from individuals from different segments of the Brazilian population. Since social security rules affect segments in an unequal way, these results can then be used to predict their impact on the sustainability of the pension system. This work takes the first step in this research effort by providing a detailed descriptive analysis of the CNIS database, pointing out its advantages and inconsistencies.
Keywords: C10; H22; H55; J26; 330; public pension; long run contribution profile; wage profile